2014
DOI: 10.1007/s13762-014-0589-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment and energy efficiency of advanced oxidation processes for the distillery wastewater

Abstract: The treatment of distillery effluent was investigated experimentally by various advanced oxidation processes such as Fenton and ozone with different combination of UV and H 2 O 2 system. The effect of operating parameters such as hydrogen peroxide concentration, initial effluent pH and Fe 2? concentration on Fenton system for the percentage color and chemical oxygen demand removal has been studied. The energy per order was also calculated for the advanced oxidation process. The ozone-photoFenton system has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…According to the IUPAC, the efficiency of an electric-energyintensive oxidation process can be measured with the electrical energy per order (EE/O, kWh m À3 order À1 ). 33 The EE/O is described as the electrical energy in kilowatt per hours required to reduce the concentration of organic pollutants by one order of magnitude in 1 m 3 contaminated water and can be calculated from the following (eqn (13) and (14)):…”
Section: Operating Cost Analysismentioning
confidence: 99%
“…According to the IUPAC, the efficiency of an electric-energyintensive oxidation process can be measured with the electrical energy per order (EE/O, kWh m À3 order À1 ). 33 The EE/O is described as the electrical energy in kilowatt per hours required to reduce the concentration of organic pollutants by one order of magnitude in 1 m 3 contaminated water and can be calculated from the following (eqn (13) and (14)):…”
Section: Operating Cost Analysismentioning
confidence: 99%
“…Different methods and technologies such as coagulation (Tan et al 2000;Chaudhari et al 2007), aerobic and anaerobic treatments (LaPara et al 2000), advanced oxidation process (Esplugas et al 2002;Asaithambi et al 2014), adsorption (Faust and Aly 1987) and electrolysis (Szpyrkowicz et al 1995;Sridhar et al 2014) have been reported to treat industrial wastewaters. These treatment processes require high capital and operating cost.…”
Section: Introductionmentioning
confidence: 99%
“…Most azo dyes are resistant to biodegradation under aerobic conditions and could be toxic to microorganisms and plants if they are discharged without proper treatment (Gupte et al 2013;Patil and Jadhav 2013;Przytás et al 2013). Studies in the literature show that advanced oxidation processes (AOPs), which generate hydroxyl radical, can rupture dye chromophore and convert recalcitrant azo dyes into carbon dioxide, water, and inorganic ions (Goi et al 2010;Zapata et al 2009Zapata et al , 2010Lopez et al 2004;Rameshraja and Suresh 2011;Shafieiyoun et al 2012;Asaithambi et al 2014). Among the AOPs studied, Fenton or photo-Fenton process has many advantages because it is a homogeneous process and favors a better contact between reagent species without mass transfer limitation.…”
Section: Introductionmentioning
confidence: 99%